The Effective Role of Targeted Therapy in Advanced Colorectal Cancer - Sarah K. Obay; Ali N. Wannas; Rana A. Ghaleb (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2022)
Though chemotherapy is the major strategy to manage patients with advanced-stage colorectal cancer (CRC), the main challenge is the progression of CRC despite using combination of different chemotherapeutic agents. So, to overcome this challenge, a new class